(untitled) (Eurasian Journal of Ecology, 2016)
Studied the fauna of water beetles – Bioregulators bloodsucking Diptera of South Kazakhstan and extermination of the average daily water beetles larvae of mosquitoes. Total noted 26 species of 6 families, 17 species of them may be of interest for biological control of biting Diptera.